The Economic Impact of Tourism and Infrastructure Development on Local Community Income: Case Study of Sembalun Tourism Destination - Jumatul Aolia; Novi Yanti Sandra Dewi; Ahadiah Agustina; Mukhlishin (Politeknik Ganesha Medan, 2026)
ABSTRACT This study aims to explore the economic impact of tourism development and infrastructure development on the welfare of local communities in Sembalun Village. The research method used is a quantitative approach with a descriptive design. The variables analyzed include tourism economy and infrastructure development as independent variables, and local community income as the dependent variable. Data were collected through a survey using a questionnaire with random sampling technique, with a sample of 100 respondents. The results showed that the tourism economy sector contributed 61.7% to the increase in community income, while infrastructure development contributed 23.3%. Simultaneously, the two variables contributed 47.9% to community income. The findings are expected to contribute to the development of sustainable and equitable tourism policies, as well as provide useful perspectives for stakeholders in formulating tourism and infrastructure-based regional development strategies. Based on the research results, it is imperative for the government and stakeholders to strengthen investment in the tourism sector as well as mutually supportive infrastructure development. Improved facilities and quality of public services, such as accessibility, transportation infrastructure, as well as the development of tourist attractions, will accelerate local economic growth and improve community welfare. Therefore, collaboration between tourism development and infrastructure development is a crucial factor in realizing sustainable and inclusive regional development. Keywords: Tourism economy, infrastructure development, local community income, Sembalun, economic development